Visco-modified osculating magnetic and electric flux surfaces in the normal direction - Körpınar, Talat; Demirkol, Rıdvan Cem; Körpınar, Zeliha (Taylor & Francis Ltd, 2022)
In this manuscript, we investigate a new technique to describe the tangent, principal normal, and binormal osculating magnetic and electric flow density in the normal direction in the ordinary space. Based on the computed flow density, we determine the Frenet-Serret vectors of the osculating magnetic and electric flow phase in the normal phase. Then, we consider the modified visco Heisenberg ferromagnetic model to observe the variation when we compare Frenet-Serret vectors of the osculating magnetic and electric flow phase due to the modified visco Heisenberg ferromagnetic. Finally, we determine the existence conditions for describing the field vectors flux surfaces under the osculating evolution equations in the normal direction.
Keywords: Osculating motion; flow density; flow phase; visco Heisenberg model; ferromagnetism